Explicit (but not implicit) environmentalist identity predicts pro-environmental behavior and policy preferences. (August 2018) - Brick, Cameron; Lai, Calvin K.
Abstract: Awareness of environmental problems has increased dramatically over recent decades, but individual action to address environmental issues has remained stagnant. Shifting social identities may be an under-appreciated explanation of this gap: identification with environmentalists in the U.S. dropped from 78% to 42% since 1991. In four pre-registered studies of U.S. residents (total N = 2, 033), we explored the predictors and outcomes of environmentalist identity . We also developed a novel implicit measure of less deliberate aspects of environmentalist identity. We used explicit and implicit environmentalist identity to predict self-reported environmental behaviors and policy preferences. Meta-analysis of our pre-registered studies revealed that explicit identity was moderately associated with implicit identity ( r = 0.24). Explicit identity strongly and uniquely predicted pro-environmental behaviors and policy preferences (partial r s = .58, .62), while implicit identity did not uniquely predict either (partial r s = .05, .05). Our findings highlight the importance of social identity in conservation. Highlights: Environmentalist identity is associated with behavior and policy preferences. We introduce a novel implicit measure of environmentalist identity. Explicit identity is a strong and unique predictor of pro-environmental action. Implicit identity is not a unique predictor of pro-environmental action. We examine dispositional predictors of environmentalist identity.